Incidence and risk factors for non-alcoholic steatohepatitis: prospective study of 5408 women enrolled in Italian tamoxifen chemoprevention trial. Issue 7497 (3rd March 2005) - Bruno, Savino; Maisonneuve, Patrick; Castellana, Paola; Rotmensz, Nicole; Rossi, Sonia; Maggioni, Marco; Persico, Marcello; Colombo, Alberto; Monasterolo, Franco; Casadei-Giunchi, Donata; Desiderio, Franco; Stroffolini, Tommaso; et al.
Abstract: Objective To assess the incidence, cofactors, and excess risk of development of non-alcoholic fatty liver disease, including non-alcoholic steatohepatitis, attributable to tamoxifen in women. Design Prospective, randomised, double blind, placebo controlled trial. Setting and participants 5408 healthy women who had had hysterectomies, recruited into the Italian tamoxifen chemoprevention trial from 58 centres in Italy. Intervention Women were randomly assigned to receive tamoxifen (20 mg daily) or placebo for five years. Main outcome measure Development of non-alcoholic fatty liver disease in all women with normal baseline liver function who showed at least two elevations of alanine aminotransferase (≥ 1.5 times upper limit of normal) over a six month period. Results During follow up, 64 women met the predefined criteria: 12 tested positive for hepatitis C virus, and the remaining 52 were suspected of having developed non-alcoholic fatty liver disease (34 tamoxifen, 18 placebo)—hazard ratio = 2.0 (95% confidence interval 1.1 to 3.5; P = 0.04). In all 52 women ultrasonography confirmed the presence of fatty liver. Other factors associated with the development of non-alcoholic fatty liver disease included overweight (2.4, 1.2 to 4.8), obesity (3.6, 1.7 to 7.6), hypercholesterolaemia (3.4, 1.4 to 7.8), and arterial hypertension (2.0, 1.0 to 3.8). Twenty women had liver biopsies: 15 were diagnosed as having mild to moderate steatohepatitis (12 tamoxifen, 3 placebo), and five had fatty liver alone (1 tamoxifen, 4 placebo). No clinical, biochemical, ultrasonic, or histological signs suggestive of progression to cirrhosis were observed after a median follow up of 8.7 years. Conclusions Tamoxifen was associated with higher risk of development of non-alcoholic steatohepatitis only in overweight and obese women with features of metabolic syndrome, but the disease, in both the tamoxifen and the placebo group, after 10 years of follow up seems to be indolent.